2016
DOI: 10.1038/srep35810
|View full text |Cite
|
Sign up to set email alerts
|

LPA receptor activity is basal specific and coincident with early pregnancy and involution during mammary gland postnatal development

Abstract: During pregnancy, luminal and basal epithelial cells of the adult mammary gland proliferate and differentiate resulting in remodeling of the adult gland. While pathways that control this process have been characterized in the gland as a whole, the contribution of specific cell subtypes, in particular the basal compartment, remains largely unknown. Basal cells provide structural and contractile support, however they also orchestrate the communication between the stroma and the luminal compartment at all develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…RNA-Seq: All statistical methods, and data analysis were conducted using the R statistical software [ 28 ] as we previously described [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA-Seq: All statistical methods, and data analysis were conducted using the R statistical software [ 28 ] as we previously described [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We found that milk stasis and loss of PMCA2 expression both upregulate TFEB expression and nuclear localization in vivo . This was associated with an increase in TFEB-regulated genes in previously published RNAseq data from involuting mouse mammary glands 44 . We also demonstrated that increased intracellular Ca 2+ increases TFEB expression and nuclear localization in mammary epithelial cells in vitro and this was also associated with an upregulation of TFEB-regulated genes based on RNAseq data.…”
Section: Discussionmentioning
confidence: 53%
“…5D, Fig.2). We also detected changes in gene expression consistent with activation of TFEB when we interrogated a RNAseq database which included mouse mammary glands harvested at day 10 of lactation and at day 2 of involution 44 . KEGG-identified gene set enrichment analysis demonstrated an increase in the expression of genes associated with lysosomes and autophagy at day 2 of involution as compared to lactation, both of which are regulated by TFEB (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, multiple additional pathways influence MG development and function that are not necessarily captured by standard endocrine-sensitive endpoints (e.g., vaginal opening, estrous cyclicity, serum hormones, reproductive organ weights). For example, multiple stages of MG development are influenced by the aryl hydrocarbon receptor [252], progesterone [2,253], prolactin [254][255][256], insulin-like growth factors [253,255,257,258], transforming growth factor-α [259], and placental lactogens [260]. While some of these factors are also involved in other aspects of reproductive development [261][262][263][264][265] and may be detected in other typically measured endpoints, the interplay of these mechanisms and magnitude of effects likely differ between tissues.…”
Section: Cross Cutting Issuesmentioning
confidence: 99%